1991
DOI: 10.1080/03670244.1991.9991162
|View full text |Cite
|
Sign up to set email alerts
|

Household economic strategies, food resource allocation, and intrahousehold patterns of dietary intake in rural Mexico

Abstract: This study examines 1) evidence for unequal intrahousehold food distribution between mothers and preschoolers and 2) the relationships of household economic strategies and resource allocation to diet. In a survey of 178 Mexican households, the following were recorded: 1) income by source and earner; 2) agricultural production and expenses; 3) household food use; and 4) frequency of consumption of 27 foods. Twelve diet recalls per individual were obtained from 47 households. Comparisons of nutrient intake and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 22 publications
(27 reference statements)
1
29
0
Order By: Relevance
“…These associations are consistent with the other analyses that we have done demonstrating interrelationships among household economic strategies, resource allocation patterns, and dietary intake (Kaiser and Dewey, 1991a;Kaiser and Dewey, 1991b). That no relationship was found between household economic strategies and some of the other measures of nutritional status is not surprising.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These associations are consistent with the other analyses that we have done demonstrating interrelationships among household economic strategies, resource allocation patterns, and dietary intake (Kaiser and Dewey, 1991a;Kaiser and Dewey, 1991b). That no relationship was found between household economic strategies and some of the other measures of nutritional status is not surprising.…”
Section: Discussionsupporting
confidence: 92%
“…In this part of Mexico, many women who earn income do so through operating small stores. Previously we have shown that ownership of a store was associated with increased use of processed foods, as compared to other economic strategies (Kaiser and Dewey, 1991b). We have also reported a relationship between the frequency of snackfood consumption and indices of fatness, but not linear growth, in these children (Kaiser and Dewey, 1989).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Of studies that have considered intra-household differences in food distribution more directly, some indicate better intakes among adults, often men, due to their higher social status, energetic expenditure and/or economic value (Abdullah & Wheeler, 1985; Engle & Nieves, 1993). Other studies have reported the preferential feeding of children (Graham, 1997; Kaiser & Dewey, 1991; Kramer et al, 1997; Leonard, 1991; Oldewage et al, 2005) and thus offer some evidence of buffering. The literature also suggests that individual-level factors, such as child age and gender, determine access to food.…”
Section: Introductionmentioning
confidence: 95%